Cross-disciplinary advance care planning in oncology and palliative care amidst a pandemic: a best practice implementation project - Muehlensiepen, Felix; Stanze, Henrikje; May, Susann; Stahlhut, Kerstin; Helm, Carolin; Hakam, Hassan Tarek; Bała, Małgorzata M; Peričić, Tina Poklepović; Vrbová, Tereza; Klugarova, Jitka; Prill, Robert (JBI evidence implementation, 2024)
INTRODUCTION: Advance care planning (ACP) ensures that patients receive medical care aligned with their values, goals, and preferences, especially regarding end-of-life decisions in serious chronic illnesses. OBJECTIVE: This project aimed to introduce and promote evidence-based ACP in oncology and palliative care at a midsized hospital near Berlin, Germany, during the COVID-19 pandemic. METHODS: This project was guided by the JBI Evidence Implementation Framework and used a mixed methods audit cycle. A baseline audit was conducted using qualitative interviews and workshops with representatives from all the health care disciplines involved in oncology and palliative care at the hospital. The findings were compared with eight best practice recommendations. Targeted strategies aimed at the key stakeholders involved in ACP practice were then implemented. Finally, a semi-quantitative questionnaire was used in a follow-up audit with the same participants as in the baseline audit. RESULTS: The baseline audit revealed a high level of familiarity with the concept of ACP. However, there was a lack of a uniformly accepted definition and understanding of ACP among the health care professionals, leading to a lack of coordination in task distribution. The follow-up audit revealed improvements with regard to education and training in ACP (Criterion 1: 50% to 100%) and organizational support to facilitate ACP conversations (Criterion 3: 87.5% to 100%). Other audit criteria compliance rates remained unchanged. CONCLUSION: Clinical education and team-based process analysis can facilitate ACP implementation across disciplines in oncology and palliative care facilities. However, the project did not succeed in implementing lasting changes in clinical processes and best practice ACP due to the COVID-19 pandemic. Such an endeavor would demand considerable resources and time, both of which were constrained during the pandemic. SPANISH ABSTRACT: http://links.lww.com/IJEBH/A236.
Keywords: lékařská praxe založená na důkazech; lékařská onkologie; pandemie; Palliative Care; lidé; Advance Care Planning; Germany; SARS-CoV-2; směrnice pro lékařskou praxi jako téma; předběžné plánování péče; Medical Oncology; Německo; paliativní péče; Pandemics; Evidence-Based Practice; Practice Guidelines as Topic; COVID-19; Humans